Isolated left ventricular non-compaction cardiomyopathy associated with ventricular preexcitation : a case report - Božić, Ivo, liječnik (Array, 2009)
Abstract: Isolated left ventricular non-compaction (ILVNC) is one of the most misclassified cardiomyopathies. It is caused by failure of normal embryonic development of the myocardium from loosely arranged muscle fibers to the mature compacted form of myocardium, but it seems that etiology is not exclusively congenital. Diagnosis of ILVNC is mostly missed because of lack of awareness and knowledge. The recognition of the disease is mandatory, because of its high mortality and morbidity due to the progressive heart failure, thromboembolic events and lethal arrhythmias. We report of a family in which two adult members were found to have ILVNC. A literature review about ILVNC pathogenesis, diagnosing, and treatment was discussed